Treatment of difficult-to-treat-dermatophytosis: results of a randomized, double-blind, placebo-controlled study - Sanjeewani Fonseka; Dilan Dileepa Jayarathne Bandara; Dasun Chathumina Wickramaarachchi; Narankotuwe Gedara Kumudu Hasanka Heshani Narankotuwa; Pallegoda Vithana Ranjith Kumarasiri (Journal of Infection in Developing Countries)
Introduction: Difficult-to-treat dermatophytosis is an emerging public health problem in Sri Lanka. Safe, effective and affordable treatment is needed to solve this problem. Therefore this study has assessed the effectiveness and safety of modified Whitfield ointment applied twice daily with oral griseofulvin 500 mg daily given over 8 weeks in patients with difficult-to-treat dermatophytosis.